1998
DOI: 10.1002/(sici)1097-4695(19981115)37:3<441::aid-neu9>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Attaining and maintaining strong vocal synapses in female Xenopus laevis

Abstract: Synaptic efficacy at the laryngeal neuromuscular synapse differs markedly in adult male and female Xenopus laevis. Here, we examined the relation between circulating estrogen and synapse strength in developing and adult female frogs. Circulating estrogen levels in males and females during juvenile and adult stages were measured using radioimmunoassays. Synaptic strength was determined by quantal analysis in isolated female larynges. In males, estrogen levels are low (<40 pg/mL) throughout development. In femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…These results indicate that NCGR frogs were still at the peak of their reproductive activity, and thus the differences in the absolute concentrations of plasma sex steroids measured in the study by Paolucci et al [35] and our study may be due to differences among species. In our study, males from the NCGR exhibited greater E2 concentrations than those reported for males from another study [41], but were similar to those in R. clamitans (control group) that were confined under laboratory conditions [42]. The reasons for these discrepancies are unknown.…”
Section: Discussionsupporting
confidence: 63%
“…These results indicate that NCGR frogs were still at the peak of their reproductive activity, and thus the differences in the absolute concentrations of plasma sex steroids measured in the study by Paolucci et al [35] and our study may be due to differences among species. In our study, males from the NCGR exhibited greater E2 concentrations than those reported for males from another study [41], but were similar to those in R. clamitans (control group) that were confined under laboratory conditions [42]. The reasons for these discrepancies are unknown.…”
Section: Discussionsupporting
confidence: 63%
“…Rapid, intensity-modulated calls require an entirely fast-twitch complement of muscle fibers, and a weak and facilitating neuromuscular synapse responsible for EMG potentiation (Ruel et al, 1998;Tobias et al, 1998). Given the widespread rapidity and intensity modulation of male advertisement calls in Xenopus and Silurana (Tobias et al, 2011), an entirely fast-twitch complement of laryngeal muscle fibers and a facilitating synapse may also represent the male ancestral state.…”
Section: Borealis Has Lost Certain Male-specific Laryngeal Charactersmentioning
confidence: 99%
“…This results in the appearance of VTG in the plasma, vitellogenic oocytes in the ovary, and the development of the oviducts (Olmstead et al, 2009d). Oviduct development appears to be regulated by estrogens as development correlates with blood E2 levels in X. laevis (Tobias et al, 1998) and X. tropicalis (Olmstead et al, 2009d). Jelly coats are applied to the outside of oocytes as they pass through the oviduct and collect in the ovisac, ready for fertilization.…”
Section: Basic Biology and Test Overviewmentioning
confidence: 99%